The Evaluation of Profitability, Corporate Social Responsibility, and Financial Risk in Asset Management Companies in Iran - Hanieh Hekmat; Farnoosh Keshavarz mirza mohammadi (تحقیقات مالی)
Objective: There are many perspectives on the interplay of profitability, Corporate social responsibility (CSR), and financial risk in different industries. The purpose of this paper is to examine the factors affecting the success of asset management companies (AMC) in Iran from a financial and social point of view. Since the asset management industry in Iran is emerging and the first AMC was founded in 2011, not much research has been conducted in this field. Therefore, this study tries to contribute to the extant literature by investigating the interactive effect of profitability, CSR, and financial risk. It also seeks to document empirical evidence in this industry.Methods: To fulfill the purposes, the researchers examined 45 AMCs licensed by the Stock Exchange and Securities Organization through cross-sectional regression models and correlation tests. Comparatively, the correlation between information related to social responsibility using KLD checklist scores and assets under management of 51 large foreign AMC was tested. The KLD checklist consisted of seven different concepts: environmental, products and services, human resources, customer ship, social, culture and belief, and energy. Previous studies used many different factors to score CSR but this study computed CSR scores following Kordestani & et al. (2018)Results: The results proved the coefficients of mutual funds management fee (especially fixed funds fee) to be higher than the coefficients of the portfolio management fee in explaining profitability. It was also found that the number of employees and the average financial risk do not impact profitability. In addition, CSR does not relate to any of the following variables; the profitability, the fees and the number of managed portfolios, the fees and the number of mutual funds, the number of companies in the group, the financial risk as well as the number of assets under management. The comparative study of 51 large foreign AMCs also revealed that compliance with CSR disclosure requirements in the world has a significant relationship with profitability.Conclusion: AMCs could be more profitable by focusing on mutual funds development than on portfolio expansion, especially if they establish a fixed fund. As a result, we suggest newcomers constitute fixed mutual funds as the first action plan. Our observation showed that the average debt ratio in the asset management industry hovered around 32%, of which 28% belonged to short-term debts. This revealed that the active AMCs mostly preferred short-term debts to long-term ones. So, we concluded that these AMCs avoided financial risk in favor of the high business risk of the industry. To provide financial success, they should enhance their network via having a vast group community and robust their beneficial activities and their synergy among the whole group. Also, due to the voluntary disclosure of CSR in Iran, there is no sufficient information and the average related information is very low (about 11%).